2022
DOI: 10.1371/journal.pone.0277612
|View full text |Cite
|
Sign up to set email alerts
|

Retrospective molecular investigation of Mayaro and Oropouche viruses at the human-animal interface in West-central Brazil, 2016–2018

Abstract: Mayaro virus (MAYV, Togaviridae) and Oropouche orthobunyavirus (OROV, Peribunyaviridae) are emerging enzootic arboviruses in Latin America. Outbreaks of febrile illness associated with MAYV and OROV have been reported among humans mainly in the northern region of Brazil since the 1980s, and recent data suggest these viruses have circulated also in more populated areas of western Brazil. MAYV shares mosquito vectors with yellow fever virus and it has been historically detected during yellow fever epidemics. Aim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 51 publications
0
2
0
Order By: Relevance
“…The short viremia period associated with arbovirus infection may result in underreporting of exposed animals if only molecular tools are used for diagnosis [ 12 ]. It is also worth mentioning that, in a previous study, MAYV and OROV RNA was not detected in these samples [ 11 ]. Therefore, serosurveys for the detection of NAb are a reliable approach to confirm enzootic arbovirus exposure during surveillance programs.…”
Section: The Studymentioning
confidence: 89%
See 1 more Smart Citation
“…The short viremia period associated with arbovirus infection may result in underreporting of exposed animals if only molecular tools are used for diagnosis [ 12 ]. It is also worth mentioning that, in a previous study, MAYV and OROV RNA was not detected in these samples [ 11 ]. Therefore, serosurveys for the detection of NAb are a reliable approach to confirm enzootic arbovirus exposure during surveillance programs.…”
Section: The Studymentioning
confidence: 89%
“…Because domestic animals are commonly found in urban and peri-urban areas, they can be exposed to arboviruses to the same extent as humans. Even though domestic animals rarely act as amplifying hosts for most arboviruses, they may be important for surveillance, due to their exposure to arthropod vectors and proximity to wildlife and humans [ 2 , 11 , 12 ]. Several studies have demonstrated that some domestic animals, such dogs and horses, may act as useful sentinels for arbovirus’ circulation [ 12 – 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…OROV glycoproteins exhibit complex topology. They are type I transmembrane proteins, signifying that they possess a single pass transmembrane domain with their N-terminus on the exterior of the cell or virion and their C-terminus on the interior ( Dias et al., 2022 ). The glycoproteins are synthesized as a precursor polyprotein that is co-translationally inserted into the endoplasmic reticulum (ER).…”
Section: Viral Genome and Replicationmentioning
confidence: 99%
“…Brazil is a hotspot for arboviral diseases, mainly due to its constellation of biodiverse ecotypes, which include: (a) the Amazon basin, encompassing the largest rainforest in the world [18][19][20][21][22], (b) the Atlantic forest, with the largest biodiversity and extending as far south and inland as Argentina and Paraguay [23][24][25][26][27], (c) the Pantanal, considered to be the largest wetland globally [6,[28][29][30][31][32][33][34], and (d) the Cerrado, a vast region of tropical savanna in eastern Brazil [35][36][37][38].…”
Section: Introductionmentioning
confidence: 99%